Flute casts and related structures on moulded silt injection surfaces in continental sandstone of the Boss Point Formation: southeastern New Brunswick, Canada - van de Poll, H.; Patel, I. (Atlantic Geology, 1981)
Flute, load and groove casta occur widely at the sharp Interfaces of siltstone dlaplrs, Inject loo Lenses, and pods la fluvial sandstone of tbe Boas Point Formation of southeastern New Brunswick. These concordant and discordant Injection features range from approximately 20 centimetres (pods) to many metres (Injection lenaes) In diameter. They are confined to "brecclform Intervals" that can be traced along strike and dip for a hundred metres or more. The flute, load and groove casts on the Injection surfaces, have evidently not been formed by any primary sedimentary process but are the result of liquefaction, sediment Injection and flow moulding during post-deposit lonal compaction of the strata. The term "rheoplaals" Is proposed to denote this process, and the general term "rhaoplascic structures" or "rheoplasts" refers to the range of sole-marking like structures formed as a result of this process. The realization that flute caata can form as a result of post-depoeltional processes is of great significance In the classification of sedimentary structure* and the Interpretation of deposltlonal environments and attendant sedimentary processes.